The social responsibility of the organizations towards employees: a pilot study within atypical NGOs in Romania - PĂCEȘILĂ Mihaela (Applied Research in Administrative Sciences)
An organisational entity (non-governmental organisation, company, public institution or authority) should not be seen socially responsible if its staff is not satisfied and motivated. However, despite many publications of social responsibility in the literature, papers focusing on the social responsibility of the organisation towards employees are rare. The following article aims to analyse the social responsibility of an atypical NGO towards its employees. In this regard, a survey conducted by using one questionnaire was used. The analysis is based on several aspects of the organisations’s social responsibility towards employees, namely recruitment and employees’ retention, employees' health and safety, effects generated by the employees’ satisfaction and dissatisfaction, reward system. The study revealed that the workplace atmosphere, the organisation’s concern towards the employees' problems, as well as the reward for their efforts leads to the increasing their loyalty and to achieving high performances.